2017
DOI: 10.1002/rmb2.12068
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of reversible male infertility due to congenital adrenal hyperplasia combined with testicular adrenal rest tumor

Abstract: CasesTesticular adrenal rest tumor (TART) is one of the possible causes of male infertility, accompanied by congenital adrenal hyperplasia (CAH). Here are reported two cases of TARTs that were referred to Kobe City Medical Center West Hospital for the treatment of infertility and testicular tumors.OutcomeIn one case, the semen analysis was improved from oligoasthenozoospermia to normozoospermia after taking oral glucocorticoid supplementation. The other case of original azoospermia showed that sperm had ejacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…TARTs in some cases and may restore fertility (637)(638)(639). However, TARTs also occur in wellcontrolled patients and only a few studies have found a clear association between hormonal control, and TARTs (437,640,641).…”
Section: Suppression Of Acth Secretion By Increased Doses Of Glucocor...mentioning
confidence: 99%
“…TARTs in some cases and may restore fertility (637)(638)(639). However, TARTs also occur in wellcontrolled patients and only a few studies have found a clear association between hormonal control, and TARTs (437,640,641).…”
Section: Suppression Of Acth Secretion By Increased Doses Of Glucocor...mentioning
confidence: 99%
“…Besides,fertility loss is deemed as the complication in TARTs cases and always related mechanical obstruction and toxic effect of local adrenal steroids or metabolites derived from adrenal rest tumors[ 23 ].In spite of infertility,some effective treatments have been proposed like follicle-stimulating hormone(FSH)/LH induction or mitotane therapy[ 24 ].In most azoospermia or oligozoospermia patients affected by CAH,there are several reversible fertility TARTs cases[ 25 ],which could provide some guidance for 3β-2HSD population.…”
Section: Discussionmentioning
confidence: 99%
“…However, TARTs have also been reported in men with adequate control of CAH and, conversely, some subjects with poorly controlled CAH never develop TARTs despite chronically elevated ACTH levels. The first choice of treatment is intensification of glucocorticoid treatment to suppress ACTH, based on a few cases in which this has led to reduction of the tumor size and improved testicular function (17)(18)(19)(20). Hydrocortisone, dexamethasone, and prednisone were all used as treatment for TARTs (21).…”
Section: Discussionmentioning
confidence: 99%